MicroRNA expression in acute myeloid leukaemia: New targets for therapy?. Issue 3 (26th April 2022) - Fletcher, Daniel; Brown, Elliott; Javadala, Julliah; Uysal‐Onganer, Pinar; Guinn, Barbara‐ann
Abstract: Recent studies have shown that short non‐coding RNAs, known as microRNAs (miRNAs) and their dysregulation, are implicated in the pathogenesis of acute myeloid leukaemia (AML). This is due to their role in the control of gene expression in a variety of molecular pathways. Therapies involving miRNA suppression and replacement have been developed. The normalisation of expression and the subsequent impact on AML cells have been investigated for some miRNAs, demonstrating their potential to act as therapeutic targets. Focussing on miRs with therapeutic potential, we have reviewed those that have a significant impact on the aberrant biological processes associated with AML, and crucially, impact leukaemic stem cell survival. We describe six miRNAs in preclinical trials (miR‐21, miR‐29b, miR‐126, miR‐181a, miR‐223 and miR‐196b) and two miRNAs that are in clinical trials (miR‐29 and miR‐155). However none have been used to treat AML patients and greater efforts are needed to develop miRNA therapies that could benefit AML patients in the future.